2016
DOI: 10.1016/j.bpj.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Amyloid β -Peptide (1-42): Tetramer Formation and Membrane Interactions

Abstract: The aggregation cascade and peptide-membrane interactions of the amyloid β-peptide (Aβ) have been implicated as toxic events in the development and progression of Alzheimer's disease. Aβ42 forms oligomers and ultimately plaques, and it has been hypothesized that these oligomeric species are the main toxic species contributing to neuronal cell death. To better understand oligomerization events and subsequent oligomer-membrane interactions of Aβ42, we performed atomistic molecular-dynamics (MD) simulations to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
89
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 90 publications
7
89
2
Order By: Relevance
“…Christensen et al examined the formation process of trimers and tetramers using a highly mobile membrane mimetic model and their simulations showed that initially membrane-bound α-helical hIAPPs can self-assemble into β-sheet structures [42]. Brown et al carried out MD simulations of disordered Aβ1–42 tetramers on zwitterionic lipid bilayers and they observed that the binding of Aβ tetramers on POPC bilayers resulted in a greater membrane perturbation than that on cholesterol-rich membranes [43]. Recently, Dong et al investigated systemically the adsorption dynamics, structural stability and membrane perturbation of protofibrillar Aβ trimers constructed using three different NMR-derived fibril structures, 2BEG, 2LMN and 2M4J.…”
Section: Introductionmentioning
confidence: 99%
“…Christensen et al examined the formation process of trimers and tetramers using a highly mobile membrane mimetic model and their simulations showed that initially membrane-bound α-helical hIAPPs can self-assemble into β-sheet structures [42]. Brown et al carried out MD simulations of disordered Aβ1–42 tetramers on zwitterionic lipid bilayers and they observed that the binding of Aβ tetramers on POPC bilayers resulted in a greater membrane perturbation than that on cholesterol-rich membranes [43]. Recently, Dong et al investigated systemically the adsorption dynamics, structural stability and membrane perturbation of protofibrillar Aβ trimers constructed using three different NMR-derived fibril structures, 2BEG, 2LMN and 2M4J.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of evidence suggesting that formation and accumulation of Aβ40 and Aβ42 in normal neuronal membranes contributes to Aβ toxicity . It is also known that mature Aβ fibrils are less toxic compared to soluble Aβ oligomers .…”
Section: Introductionmentioning
confidence: 99%
“…Aβ oligomer intermediates are predominantly composed of β‐sheet structures and are known to trigger Aβ toxicity via several mechanisms . A number of studies have revealed the contributions of Aβ toxic mechanisms to the pathology of AD, including formation of Aβ oligomers promoting the generation of reactive oxygen species, excessive aggregation of Aβ proteins inducing stress in the endoplasmic reticulum, disruption of neuronal cell membrane integrity, and the “amyloid channel hypothesis” that describes the direct insertion of Aβ into membranes, formation of β‐barrel and pore‐like structures,, and disruption of calcium homeostasis …”
Section: Introductionmentioning
confidence: 99%
“…To get mechanistic insights into membrane disruption by toxic amyloids in atomic detail, several computational groups have investigated the interactions of Aβ oligomers with lipid bilayers by performing molecular dynamics (MD) simulations 4147 . Jang et al examined the structural properties of modeled Aβ 9–42 /Aβ 17–42 channels in zwitterionic POPC lipid bilayers and obtained Aβ channel conformations with diameters consistent with AFM measurements 41, 4850 .…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations by Poojari et al demonstrated that compared to transmembrane Aβ 1–42 monomers, membrane-embedded β-sheet-rich tetramers increased the water flow through the POPC bilayers 44 . Brown et al reported that the binding of disordered Aβ 1–42 tetramers on POPC membranes resulted in a greater membrane perturbation than that on cholesterol-rich membranes 47 . Multiple 80-ns MD simulations by Yu et al showed that the interactions of protofibrillar Aβ 17–42 pentamers with a mixed POPC and POPG membrane are stronger than those with POPC membranes 45 , indicative of the role of surface charge in Aβ-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%